Diversity and Zonation of Benthic Amphipod Crustaceans Affected by the Mississippi Submarine Canyon in the Northern Gulf of Mexico - Soliman, Yousria S.; Rowe, Gilbert T.; Wicksten, Mary; Wei, Chih-Lin (Frontiers in Marine Science, 2022)
Amphipod crustacean diversity and zonation are described from the large Mississippi Canyon that extends from the continental shelf across the entire continental margin. Benthic amphipods were sampled on four cruises from 2000-2004 from six locations in the Mississippi Canyon from depths of 480 through 2750 m, and compared with five locations in a second transect on the open continental slope approximately 100 km west of the canyon to assess the canyon effect on the structure and composition of amphipod assemblages. Five replicates were collected from each location using 0.2 m-2 GOMEX box corer. Amphipods amounted to 40% of the total faunal abundance within the canyon compared to only 4% in the non-canyon samples. Of the seventy-two species (19 families) collected, 61 were encountered in the canyon compared to 38 on the non-canyon transect. The trough-like head of the canyon (480 m) supported high densities (4,446 – 26,933 ind./m2) of the filter feeding, tube dwelling ampeliscid amphipod (Ampelisca mississippiana Soliman and Wicksten 2007), the highest densities sampled compared to any other single species, at any other location, either within or outside the canyon, reflecting extreme flux of organic detritus from the continental shelf. The dominance by this single species suppressed the within – habitat (alpha) diversity and evenness, compared to relatively high diversity within the 1000-1500 m depths interval both in and outside the canyon. The species richness and alpha diversity exhibited mid-depth maxima at ca. 1100 m both in and out of the canyon. High species richness (61) over the entire length of the canyon is presumed to be a function of greater topographic complexity and intermittent mass wasting of sediment down the canyon axis. The absence of nestedness is attributed to the amphipod reproductive pattern that lacks dispersive larval stages and brooding comparatively small numbers of eggs in this taxon. Despite depressed diversity at the head of the canyon, the fact that the number of amphipod species in the Mississippi Canyon was 1.5 times their numbers on the adjacent slope suggests that this physiographic feature enriches geographic-scale species diversity.